Digital Battlescapes: Assessing ASEAN’s Readiness for Cyber War in the Geopolitical Arena - Ahmad Ali Afandi; Hammad Isyroqunnajah; Badrus Sholeh (Department of International Relations, Brawijaya University, 2025)
This study explores the dynamics of national cyber readiness and the geopolitical dimension of cyber warfare in the Southeast Asian region, with a special focus on ASEAN member developing countries. The study is divided into four main focuses. First, the dimension of national cyber readiness is analyzed through parameters such as national policies, technical capacity, human resources, and legal and institutional frameworks. Second, the cyber threat profile in Southeast Asia is mapped based on attack trends, threat actors (both state and non-state), and critical infrastructure vulnerabilities. Third, the research examines how cyber warfare is not only a technical issue, but also a new arena of geopolitical contestation between countries, including the involvement of major actors such as China and the United States in creating influence through technology and digital networks. Fourth, the evaluation of the readiness of developing countries in ASEAN is carried out using a comparative approach, examine cyber readiness indicators from countries such as Indonesia, Vietnam, and the Philippines. The results show that despite increased awareness and policy initiatives, there are still significant gaps in cyber readiness between countries, especially in terms of resources, regional coordination, and detection-response capabilities. This research recommends strengthening collaboration between ASEAN countries in cybersecurity, establishing an integrated regional framework, and strategic investment in the development of local talent and technology. These findings are expected to contribute to the formulation of more adaptive and inclusive cyber policies in the Southeast Asian region.